Knowledge management in project environments - C. J. Pretorius; H. Steyn (South African Journal of Business Management, 2005)
Knowledge management is widely acclaimed to be a source of considerable financial advantage for organisations. Various authors realise that project environments could also benefit from the creation and re-use of knowledge, including from the lessons learned that should be documented during project close-out. Projects face specific challenges (limited time spans, changing and dispersed teams) and the reduction of project risk, time and cost through knowledge management, may well prove worthwhile.This paper reviews the literature on knowledge management, both in organisations in general and in project environments specifically. A framework for knowledge management is derived from literature. The paper also reports on an investigation of knowledge management practices in four cases within a single South African business environment. Knowledge management practices similar to ones reported abroad were found.A model is proposed for the management of knowledge in project environments, both within a single project (intraproject) and between projects (inter-project) and. guidelines for knowledge management in project environments are provided. It is also suggested that, while the management of explicit knowledge is common in project management, more attention should be given to the sharing of tacit knowledge through human interaction.
Keywords: 650